Seizure-induced unilateral posterior dislocation of the shoulder: a diagnosis not to be missed. (28th March 2018) - McKean, Andrew Roy; Kumar, Shankar; McKean, Greg Michael; Tzias, Demitrios
Abstract : A man in his mid-50s with a history of bladder carcinoma presented to the Emergency Department (ED) following a witnessed tonic–clonic seizure. Computed Tomography (CT) scanning of his brain revealed an indeterminate mass lesion in the left parietal region. The patient described bilateral shoulder pain prompting plain film radiographs with axial views, but no obvious abnormality was identified by the ED staff. Staging CT scanning did not reveal any evidence of underlying malignancy but revealed dislocation of the left humeral head with a large reverse Hill-Sachs lesion and posteriorly displaced reverse Bankart lesion. Manipulation under anaesthesia and closed reduction of the left shoulder was undertaken successfully. This case report reminds the clinician to maintain a high index of suspicion for posterior dislocation of the shoulder following seizures and to perform appropriate imaging promptly.